Part coated with hydrogenated amorphous carbon coating on undercoat comprising chromium, carbon and silicon
A sub-layer with controlled Si/Cr and C/Si ratios, combined with a vacuum deposition process, enhances the adhesion of hydrogenated DLC coatings on metal substrates, addressing the issue of poor adhesion in existing methods and achieving durable coating performance.
Patent Information
- Application Number
- JP2024209461
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-06-18
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-18
AI Technical Summary
Existing methods for depositing hydrogenated DLC coatings with a Cr, CrN, and aC:H:Si transition layer on metal substrates result in poor adhesion performance, as evidenced by low Rockwell indentation ratings and subsequent degradation, necessitating improved deposition techniques.
A method involving a sub-layer with specific atomic ratios of silicon to chromium (Si/Cr) between 0.35 and 0.60 and carbon to silicon (C/Si) between 2.5 and 3.5, applied between the metal substrate and the amorphous carbon coating, along with a vacuum deposition process using controlled plasma parameters and a chromium-based layer, to enhance adhesion.
The proposed method achieves stable and durable adhesion of the DLC coating, achieving HF1 rating in Rockwell indentation tests and improving the longevity of the coating.
Smart Images

Figure 2025065561000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated component comprising a metal substrate coated with a sub-layer and a coating of hydrogenated amorphous carbon, the coating being deposited on a sub-layer comprising chromium, carbon and silicon. [Background technology]
[0002] Parts comprising coatings which are considered here are, for example, friction components from the automotive, aviation or, for example, space sectors. In the automotive sector, these may be, for example, finger followers, tappets or distributing parts such as cams, which reduce friction between the parts, piston pins, which reduce their wear and protect the surface against dragging. The coatings described herein may also be applied to components such as piston rings, piston skirts, and liners. In the foregoing non-limiting examples, coatings are often required to operate in lubricated environments. In nature, amorphous carbon coatings, whether hydrogenated or not, have numerous applications that are not limited to components for the automotive, aviation or space industries. Guiding or sliding members, such as molds in the plastics industry, can also be coated with such coatings to minimize wear and friction without lubricants.
[0003] Amorphous carbon coatings are commonly called "DLC" (for "diamond-like carbon"). They refer to carbon-based materials obtained by vacuum deposition techniques, generally in the form of thin layers. These coatings can, for example, be divided into two types: those containing hydrogen (H) and those not containing hydrogen. Among the hydrogen-containing coatings, DLC coatings of great industrial interest are the "aC:H" coatings ("aC:H" stands for "hydrogenated amorphous carbon"). These coatings are generally produced by plasma-assisted chemical vapor deposition of carbon-based gaseous precursors, such as acetylene (C2H2). Among the hydrogen-free coatings, DLC coatings of great industrial interest are the "aC" coatings ("aC" stands for "amorphous carbon"), which are generally produced by magnetron sputtering of a graphite target, and especially the "ta-C" coatings ("ta-C" stands for "tetrahedral amorphous carbon"), which are generally produced by arc evaporation of a graphite target.
[0004] Thus, the three types of coating mentioned above are obtained by different techniques. Also, currently, for each type of DLC coating as mentioned above (formed by different techniques as explained above), it is often necessary to use a special sub-layer to ensure that the coating adheres to a given substrate. In particular, in the case of hydrogenated DLC coatings, or aC:H, there are different forms of deposition techniques that produce these coatings based on the dissociation of hydrocarbon gases. Historically, one of the processes used to deposit hydrogenated DLC is described in document FR2922358. This document concerns a method for the surface treatment of parts using a plasma element source by electron cyclotron resonance. This method results in DLC coatings of impeccable quality. However, for economic competitive reasons, it is desirable to advance the technology to obtain more efficient and therefore more competitive methods.
[0005] For that purpose, for example, document FR 2 995 493 describes a more efficient device that allows, in particular, a better adapted transfer of the plasma to the part so that the rate of DLC deposition is doubled.To this end, the deposition device includes a plasma source, the use of which is very well adapted to produce DLC coatings such as those described in document FR 2 975 404 (and also certain forms of coatings which further include a layer of chromium Core, or a layer of chromium and a layer of chromium nitride CrN, in advance). However, coatings comprising a layer of Cr, followed by a layer of CrN, then a transition layer of hydrogenated DLC doped with silicon (aC:H:Si) and finally a coating of hydrogenated DLC (aC:H) as described in document FR3011305 cannot be deposited with satisfactory properties using the device described in document FR2995493. In particular, such coatings produced from such sources often show poor performance when the coating is scored with 150 kg (kilograms) using the Rockwell method to evaluate the adhesion according to the VDI3198 standard. At a minimum, the indentations are graded HF3 according to that VDI3198 standard (this is considered rather poor, good results are graded HF1 and the worst are graded HF6). Observation of the indentations a few hours after they were made showed a natural degradation of the indentation rating towards HF6.
[0006] To alleviate this problem, the process parameters were adjusted, in particular by reducing the current of ions delivered to the part by the plasma source via a reduction in the power applied to the plasma source, and by reducing the energy of the ions via the bias voltage, in order to reduce the stress on the transition layer of silicon-doped hydrogenated DLC (aC:H:Si). The improvements observed are not sufficient to obtain coatings with a satisfactory Rockwell indentation. The plasma source is not effective enough to make the deposition conditions mild enough for the layer of "aC:H:Si". [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2007-314838 A [Patent Document 2] JP 2016-084516 A Summary of the Invention [Problem to be solved by the invention]
[0008] As a result, the present invention is directed to at least partially overcoming the above-mentioned shortcomings. In particular, one object of the present invention is to provide a component including a hydrogenated DLC coating, in particular of the aC:H type, which makes it possible to address the characteristics of the plasma of origin described in document FR2995493. The present invention therefore relates to providing a part comprising a hydrogenated DLC coating, in particular of the aC:H type, which makes it possible to obtain good performance in the adhesion test of DLC coatings by Rockwell C indentation. [Means for solving the problem]
[0009] For that purpose, according to a first embodiment, a method is provided comprising a metal substrate, a hydrogenated amorphous carbon coating of the aC:H type covering the substrate, and a sub-layer based on chromium (Cr), carbon (C) and silicon (Si) arranged between the metal substrate and the amorphous carbon coating and on which the amorphous carbon coating is applied, the sub-layer having at its interface with the amorphous carbon coating (i.e. at the surface of the sub-layer) the following atomic ratios: - the ratio of silicon content to chromium content (Si / Cr) between 0.35 and 0.60, and - Ratio of carbon content to silicon content (C / Si) between 2.5 and 3.5 A component is provided, comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Such sub-layer compositions have a content that is representative of, for example, EDX analysis (EDX is Energy Dispersive X-ray Spectroscopy or X-ray Energy Scattering Analysis) in a Scanning Electron Microscope (SEM) or that can be measured by GDOES (Glow Discharge Optical Emission Spectroscopy). It is found that such a sub-layer makes it possible to obtain a coating adhesion result that is stable over time and is rated HF1.
[0011] Moreover, such a sub-layer has also proven to be particularly advantageous for non-hydrogenated DLC coatings, in particular those of the ta-C type, or even those of the aC type. Such sub-layers therefore take the form of graded layers having compositions mainly based on chromium (Cr), silicon (Si) and carbon (C). The sub-layers are progressively enriched in silicon (Si) and carbon (C) (from the substrate towards the DLC coating) to achieve a composition that allows for adhesion of the coating as described above. In certain instances, the ratio of silicon content to chromium content (Si / Cr) of the sublayer near the interface with the DLC is between 0.38 and 0.60, or even between 0.40 and 0.60. In certain instances, the ratio of carbon content to silicon content (C / Si) of the sublayer near the interface with the DLC is between 2.8 and 3.2, or even between 2.9 and 3.1. The sub-layer may include nitrogen (N), which is particularly advantageous when the component further includes a layer of chromium nitride, as described below. Thus, in an advantageous exemplary embodiment, the sub-layer further comprises atoms of nitrogen (N), and the ratio of the nitrogen content to the chromium content (N / Cr) is less than 0.70 near the interface with the DLC, i.e., at the interface between the sub-layer and the amorphous carbon coating.
[0012] According to an advantageous embodiment, the ratio of the nitrogen content to the chromium content (N / Cr) is between 0.26 and 0.70, or even between 0.29 and 0.67, or even between 0.35 and 0.65, at the interface between the sublayer and the amorphous carbon coating. According to an advantageous embodiment, the ratio of the silicon content to the chromium content (Si / Cr) is between 0.40 and 0.55, or even between 0.45 and 0.55, at the interface between the sublayer and the amorphous carbon coating. In a preferred embodiment, the sub-layer, whether or not it contains nitrogen, has a thickness of a few tenths of a micrometer, preferably less than about 1.1 μm, for example between about 0.2 μm and 1.1 μm, preferably between about 0.3 μm and 0.6 μm.
[0013] As a practical matter, above 1.1 μm column-like development occurs which is detrimental to the retention of the sublayer, below 0.2 μm the sublayer does not provide the conformal layer effect. The amorphous carbon coating has a thickness, for example, of approximately 0.3 μm, or even approximately 0.5 μm, or even approximately 1 μm, or even 1.5 μm or more. The amorphous carbon coating may for example have a thickness of about 10 μm, or even 8 μm, or perhaps even about 3.5 μm or less. The amorphous carbon coating may for example have a thickness of about 1.5 μm to about 3.5 μm, but may be as much as 8 μm when such a coating is applied to, for example, a piston ring.
[0014] The metal substrate may be, for example, steel or other metal alloy. In an advantageous exemplary embodiment, the component further includes a chromium-based layer deposited on the substrate and having a sub-layer formed thereon. The chromium-based layer is for example a layer of chromium (Cr) and / or a layer of chromium nitride, such as CrN or Cr2N, or any intermediate compound. Preferably, the part comprises a layer of chromium (Cr), or a layer of chromium (Cr) followed by a layer of chromium nitride (eg CrN or Cr2N, or any intermediate compound). Preferably, the chromium-based layer has a thickness of a few tenths of a micrometer, preferably approximately 1 μm, or even 0.6 μm or less, for example approximately 0.1 μm to 0.5 μm, or even approximately 0.3 μm to 0.5 μm.
[0015] Furthermore, it has been found that the sub-layer can have a thinner thickness than prior art sub-layers, thereby allowing for an increased thickness of the DLC for the same total thickness of the coating (i.e. taking into account the thicknesses of the DLC, the sub-layer and optionally the chromium-based layer). In other words, the ratio of the thickness of the amorphous carbon coating to the thickness of the sub-layer, or even taking into account the thickness of the chromium-based layer (thickness of DLC / thickness of sub-layer, or thickness of DLC / (thickness of sub-layer+thickness of chromium-based layer)) can be increased, for example from about 2.2 to about 12, or even from about 2.25 to about 11.5, or even from about 2.25 to 7.5, or even from about 2.27 to about 7.25. For example, the ratio of the thickness of the amorphous carbon coating to the total thickness of the coating (i.e., here the sum of the thicknesses of the amorphous carbon coating, the sub-layer and optionally the chromium-based layer), i.e., [DLC thickness / (DLC thickness+sub-layer thickness+chromium-based layer thickness)], is from about 0.65 to about 0.9, or even from about 0.69 to about 0.88. For example, the total thickness of the coating (ie, the sum of the thicknesses of the amorphous carbon coating, the sub-layer and optionally the chromium-based layer) is from about 1.5 μm to about 4.9 μm, preferably from about 1.8 μm to about 4.6 μm.
[0016] The table below presents the various tests numbered 1 to 15. The atomic ratios measured by EDX are of the sublayer near the interface with the coating (note that the sublayer exhibits a compositional gradient, the targeted composition is towards the interface with the DLC coating). [Table 1]
[0017] In all tests, it is observed that the adhesion behavior of DLC on the sublayer is related to the surface composition of the sublayer. The presence of nitrogen on the surface is not critical for the adhesion of DLC. In fact, with similar nitrogen ratios (N / Cr) (Examples 9, 12 and 13), adhesion can be judged as good or bad. A relatively strong presence of nitrogen can have a negative effect on adhesion, as in Example 11. The absence of nitrogen can result in good adhesion (Examples 4-6, 14 and 15) or no adhesion (Examples 1-3, 7, 8). In contrast, the ratio of chromium to silicon turns out to be a more decisive factor: a relatively high chromium content relative to silicon (low Si / Cr) does not appear to be suitable for adhesion (e.g., Examples 1-3), and a relatively low chromium content relative to silicon (high Si / Cr) does not appear to be suitable for adhesion of DLC either (e.g., Examples 7-8). Thus, when the Si / Cr composition ratio was between 0.35 and 0.6, all DLC layers deposited on these sub-layers were found to be adherent (Examples 4, 5, 6, 9, 10, 13, 14 and 15).
[0018] To obtain the coatings described above, a vacuum deposition apparatus as described below is used. A vacuum deposition apparatus primarily includes a chamber, a pumping system, and a heating system, which are configured to pump and heat the part (substrate), accelerate the desorption of gases in the chamber, and quickly obtain a vacuum in the chamber that is considered to be of good quality. The deposition apparatus further comprises a substrate carrier, which is suited in terms of geometry, electrical bias and kinematics to the component, or to the portion of the component to be coated. The vacuum deposition apparatus also includes an ion stripping system configured to bombard the part to be coated (substrate) with argon (Ar) ions to remove the passivation layer that is typically present on the metal substrate to be coated. The vacuum deposition apparatus also includes a magnetron cathode with a chromium target to produce a chromium-based layer. Preferably, the ion stripping system is configured to operate simultaneously with the magnetron cathode such that the end of the ion stripping is utilized to pre-sputter the magnetron cathode with a chromium target.
[0019] For example, a plasma source such as that described in document FR2995493 can be implemented to effect an effective ion stripping of the parts to be coated in order to coat them with a DLC coating of the aC:H type. The step of depositing the sub-layer may be configured to produce a sub-layer having a composition, for example, as described above. The step of depositing the sub-layer may be configured to produce a sub-layer having a thickness, for example, as also described above. In one embodiment, the method may include a step of depositing metallic chromium, for example a step of sputtering chromium, which may include a step of introducing nitrogen simultaneously with the sputtering of chromium, so as to obtain a layer of chromium nitride, for example CrN or Cr2N, or any intermediate compound.
[0020] Such nitrogen-containing chromium-based layers are deposited as described above to a thickness of a few tenths of a micrometer. The deposition continues with the introduction of an organosilicon gas, i.e. the easiest to carry out, a gas containing at least silicon, usually tetramethylsilane (also called TMS, of formula (Si(CH3)4), which may contain traces of oxygen), or a mixture of silane and hydrocarbon. Although not exclusive, TMS is used with great preference due to its relatively high chemical stability and its high volatility, which allows easy implementation using mass flow meters. In the case of prior deposition of a chromium-based layer (Cr, and / or CrN or Cr2N), the organosilicon gas is introduced at a rate that increases to a flow rate such that the silicon content of the sublayer is at least equal to approximately 0.35 times its chromium content and at most approximately 0.60 times the chromium content near the interface. In parallel, the ratio of the carbon content to the silicon content is 2.5 to 3.5 near the interface.
[0021] When using a chromium-based layer containing nitrogen, the amount of nitrogen injected can be gradually reduced as the amount of organosilicon gas increases. The amount of nitrogen does not necessarily have to be zero, but it should be significantly less than the amount of organosilicon gas. The nitrogen introduced to produce a layer of CrN (or Cr2N) can also be abruptly reduced to zero before introducing the organosilicon precursor. Nevertheless, the gradual reduction of nitrogen is a preferred embodiment, as it allows for a gradual transition of nitrogen within the sublayer. For example, if a layer of CrN is considered, then N / Cr has a value of, for example, 1, and therefore the amount of nitrogen is probably excessive. If a layer of CrN is considered, then N / Cr has a value of, for example, 0.5, and in such a case this ratio may be maintained. During the deposition of the various thin layers (chromium-based layers, sub-layers or eg DLC coatings) in vacuum as described above, the bias voltage of the substrate carrier is typically set to -50V to -100V (volts). The partial pressure of argon during deposition of these layers is preferably set to 0.2 Pa to 0.4 Pa.
[0022] Once the flow rate of the organosilicon gas has reached the required level, the magnetron cathode is switched off and the reactive gases (i.e. organosilicon gas or organosilicon gas and nitrogen, as the case may be). If argon flow is provided, it is reduced to a low value or even to zero, acetylene is introduced and deposition of the aC:H coating begins using the plasma source described in document FR2995493. The voltage of the acceleration of the ions onto the part is set to obtain the desired characteristics of the aC:H deposition. According to the state of the art, the higher the absolute voltage, the harder the aC:H deposition.
Claims
1. The method includes the steps of: a metal substrate, a hydrogenated amorphous carbon coating of a-C:H type coating the substrate; and a sub-layer based on chromium (Cr), carbon (C) and silicon (Si) disposed between the metal substrate and the amorphous carbon coating and having the amorphous carbon coating thereon, the sub-layer having the following atomic ratios at the interface with the amorphous carbon coating: - a ratio of the silicon content to the chromium content (Si / Cr) between 0.35 and 0.60, and - a ratio of carbon content to silicon content (C / Si) between 2.5 and 3.5 A part comprising:
2. 2. The component according to claim 1, characterized in that the ratio of the silicon content (Si) to the chromium content (Cr) (Si / Cr) of the sublayer is between 0.38 and 0.
6.
3. Component according to claim 1 or 2, characterized in that the ratio (C / Si) of the carbon content (C) to the silicon content (Si) of the sub-layer is between 2.8 and 3.2, or even between 2.9 and 3.
1.
4. 4. The component according to claim 1, wherein the sub-layer further comprises atoms of nitrogen (N), and wherein the ratio of the nitrogen content to the chromium content (N / Cr) is less than 0.70 at the interface between the sub-layer and the amorphous carbon coating.
5. 5. The component according to claim 4, characterized in that at the interface between the sub-layer and the amorphous carbon coating, the ratio of the nitrogen content to the chromium content (N / Cr) is between 0.26 and 0.70, and the ratio of the silicon content to the chromium content (Si / Cr) is between 0.40 and 0.
55.
6. 6. The component according to claim 1, wherein the sublayer has a thickness of less than or equal to 1.1 μm, for example between 0.2 μm and 1.1 μm, preferably between 0.3 μm and 0.6 μm.
7. Component according to any one of the preceding claims, characterized in that the amorphous carbon coating has a thickness of 0.3 μm, or even 0.5 μm, or possibly even 1 μm or more.
8. 8. A component according to claim 1, wherein the amorphous carbon coating has a thickness of between 1.5 μm and 3.5 μm.
9. The substrate further includes a chromium-based layer having a sublayer formed thereon, the chromium-based layer being a layer of chromium (Cr) and / or a layer of chromium nitride, e.g., CrN or Cr. 2 9. The part according to claim 1, characterized in that it is a layer of N, or any intermediate compound.
10. Component according to any one of the preceding claims, characterized in that the chromium-based layer has a thickness of a few tenths of a micrometer, preferably 1 μm, or even less than 0.6 μm, for example between 0.1 μm and 0.5 μm, or even between 0.3 μm and 0.5 μm.
Citation Information
Patent Citations
Method for manufacturing carbon film
JP2007314838A
Plasma surface treatment device
JP2016084516A